Inhibition of heat shock protein 90 destabilizes receptor tyrosine kinase ROR1 in lung adenocarcinoma. Issue 3 (27th January 2021) - Khaledian, Behnoush; Taguchi, Ayumu; Shin‐ya, Kazuo; Kondo‐Ida, Lisa; Kagaya, Noritaka; Suzuki, Motoshi; Kajino, Taisuke; Yamaguchi, Tomoya; Shimada, Yukako; Takahashi, Takashi
Abstract: We have previously identified receptor tyrosine kinase‐like orphan receptor 1 (ROR1) as a direct transcriptional target of TTF‐1 / NKX2‐1, a lineage‐survival oncogene in lung adenocarcinoma. ROR1 sustains prosurvival signaling from multiple receptor tyrosine kinases including epidermal growth factor receptor, MET, and insulin‐like growth factor 1 receptor in part by maintaining the caveolae structure as a scaffold protein of cavin‐1 and caveolin‐1. In this study, a high throughput screening of the natural product library containing 2560 compounds was undertaken using a cell‐based FluoPPI assay detecting ROR1‐cavin‐1 interaction. As a result, geldanamycin (GA), a known inhibitor of heat shock protein 90 (HSP90), was identified as a potential inhibitor of ROR1. Geldanamycin, as well as two GA derivatives tested in the clinic, 17‐allylamino‐17‐demethoxygeldanamycin (17‐AAG) and 17‐dimethylaminoethylamino‐17‐demethoxygeldanamycin (17‐DMAG), decreased ROR1 protein expression. We found that ROR1 physically interacted with HSP90α, but not with other HSP90 paralogs, HSP90β or GRP94. Geldanamycin in turn destabilized and degraded ROR1 protein in a dose‐ and time‐dependent manner through the ubiquitin/proteasome pathway, resulting in a significant suppression of cell proliferation in lung adenocarcinoma cell lines, for which the kinase domain of ROR1, but not its kinase activity or N‐glycosylation, was required. Our findings indicate that HSP90 is required to sustain expression of ROR1 crucial for lung adenosarcoma survival, suggesting that inhibition of HSP90 could be a promising therapeutic strategy in ROR1‐positive lung adenocarcinoma. Abstract : High throughput screening of the natural product library was carried out using a cell‐based FluoPPI assay detecting ROR1‐cavin‐1 interaction. As a result, geldanamycin, a known inhibitor of heat shock protein 90 (HSP90), was identified as a potential inhibitor of ROR1. Our findings indicate that HSP90 is required to sustain expression of ROR1 crucial for lung adenosarcoma survival, suggesting that inhibition of HSP90 could be a promising therapeutic strategy in ROR1‐positive lung adenocarcinoma.